Media Education in Sri Lanka - Raguram, S.; Wijeyananda, R. (Asia Journalism and Mass Communication Forum 2016, 2016)
Media education was started as a job oriented course and part of a learning literature in Sri Lankan Universities four decades ago. Ahead of that, there were several training sessions for journalists were carried out by the editors and publishers of the media outlets. After forty three years, at presently, it is evolved in magnificent way: five national universities are conducting special degree programmes in Mass Communication / Media Studies and, in parallel several courses in various levels are being conducted by many organizations with different aims and objectives. Addition to this development, from year 2007 onward school level media education was started and followed by considerable number of students with the growing attention and interest. At this juncture, the study paper tried to consider the different dimensions of these developments and analyzed the strengths, weakness, opportunities and threats and proposes suggestions and recommendations to overcome the practical barriers efficiently.
Keywords: Mass communication; Journalism; Media Studies; Media Industry